Perinatal asphyxia in the term newborn - Roberto Antonucci (Journal of Pediatric and Neonatal Individualized Medicine, 2014)
Despite the important advances in perinatal care in the past decades, asphyxia remains a severe condition leading to significant mortality and morbidity. Perinatal asphyxia has an incidence of 1 to 6 per 1,000 live full-term births, and represents the third most common cause of neonatal death (23%) after preterm birth (28%) and severe infections (26%). Many preconceptional, antepartum and intrapartum risk factors have been shown to be associated with perinatal asphyxia.